2020
DOI: 10.3390/met10091119
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction and Reduction of Hat-Shaped Part Springback Made of Dual-Phase AHSS Steel

Abstract: The springback in the sheet metal forming process refers to the change of shape after the load removal. It is usually undesirable, causing problems in the subsequent forming operations, in the assembly and negatively affects the quality of the final product. Numerical prediction of the springback with the use of the numerical simulation is crucial for the reduction of forming tool try-outs, reducing manufacturing costs and increasing the accuracy of the stamped part. In this work, numerical simulation was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Today it is feasible to use finite element analysis for a more accurate prediction of the springback effect [11,12]. The finite element analysis (FEA) is a modern tool that can help to achieve more accurate springback predictions [13,14]. Several authors conducted experiments and simulations regarding springback investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Today it is feasible to use finite element analysis for a more accurate prediction of the springback effect [11,12]. The finite element analysis (FEA) is a modern tool that can help to achieve more accurate springback predictions [13,14]. Several authors conducted experiments and simulations regarding springback investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical results showed that the hardening law has a substantial impact on the results of the bulge test simulation, and thickness prediction of the bulge test specimen. The hardening model describes the development of the plasticity surface during deformation/forming (changes in its size, shape, and/or its displacement) [ 4 ]. The calculations indicate a higher correlation of the Hollomon hardening law with the experimental results when the Hill48 yield criterion is also used in the simulation ( Table 5 and Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Car body weight reduction requirements reduce fuel consumption and thus reduce CO 2 emissions. It is for the above-mentioned reasons that steel sheets with higher strength properties, which are characterized by good plasticity, have been widely used in recent years in the production of car bodies [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…That is why quite a lot of papers deal with the effect of these parameters on the springback prediction. Mulidrán et al [43,44] combined different yield criterions and hardening laws to determine the accuracy of springback prediction, in these cases for DP steel and aluminium alloy AA6451, respectively. Trzepiecinski and Lemu [45] studied the springback behaviour of steel DC04 under the different input parameters (geometry, conditions and material) for FEA (here, Abaqus).…”
Section: Introductionmentioning
confidence: 99%